Organ preservation strategies for rectal cancer treatment: tarts or trap? - ZHOU Yihang, ZENG Ziwei, KANG Liang (Waike lilun yu shijian)
Total mesorectal excision (TME) is the standard treatment for advanced mid- and low-rectal cancer. However, the associated surgical complications and subsequent impairment of organ function limit its application. In recent years, with advancements in neoadjuvant chemoradiotherapy and the implementation of immunotherapy, the pathological complete response (pCR) rate following neoadjuvant therapy for rectal cancer has significantly increased. This has raised questions about the necessity of performing TME in patients who achieve pCR. So as to, the clinical exploration of organ preservation strategies without radical surgery has been used in clinic. Current limited studies indicated that approaches such as watch & wait (W&W) or local excision have shown promising results in terms of long-term survival, and reduced surgical complications and functional impairment in some patients. However, challenges remain, including the difficulty in accurately assessing clinical complete response and the high rate of local recurrence, which could potentially compromise long-term survival. Further research into organ preservation strategies is needed, and careful consideration should be given to individual cases to prevent these strategies from becoming more of a “trap” than a “tart”.